2002
DOI: 10.1073/pnas.082515999
|View full text |Cite
|
Sign up to set email alerts
|

Otoancorin, an inner ear protein restricted to the interface between the apical surface of sensory epithelia and their overlying acellular gels, is defective in autosomal recessive deafness DFNB22

Abstract: A 3,673-bp murine cDNA predicted to encode a glycosylphosphatidylinositol-anchored protein of 1,088 amino acids was isolated during a study aimed at identifying transcripts specifically expressed in the inner ear. This inner ear-specific protein, otoancorin, shares weak homology with megakaryocyte potentiating factor͞ mesothelin precursor. Otoancorin is located at the interface between the apical surface of the inner ear sensory epithelia and their overlying acellular gels. In the cochlea, otoancorin is detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
154
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 36 publications
2
154
0
1
Order By: Relevance
“…This microarray increases our chances of finding new or novel genes involved in hearing or in development of the ear. As demonstrated in this study, four differentially expressed genes, Otoa, Otor, Otos, and Tmprss3, were identified that are associated with hearing impairment ( Zwaenepoel et al 2002). Although a number of unidentified singletons exhibited differential expression in the LW, OC, or SG, none were found to colocalize with a deafness locus Pompeia et al 2004).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This microarray increases our chances of finding new or novel genes involved in hearing or in development of the ear. As demonstrated in this study, four differentially expressed genes, Otoa, Otor, Otos, and Tmprss3, were identified that are associated with hearing impairment ( Zwaenepoel et al 2002). Although a number of unidentified singletons exhibited differential expression in the LW, OC, or SG, none were found to colocalize with a deafness locus Pompeia et al 2004).…”
Section: Discussionsupporting
confidence: 50%
“…(Otoa) and transmembrane serine protease 3 (Tmprss3), which are both implicated in autosomal recessive deafness Zwaenepoel et al 2002). Also included are otoraplin (Otor), a possible deafness gene associated with the otic capsule (Cohen-Salmon et al 2000), and otospiralin (Otos), which leads to hair cell degeneration and deafness in guinea pigs when downregulated (Delprat et al 2002).…”
Section: Differential Expression Analysesmentioning
confidence: 99%
“…Scx is expressed in interdental cells of the spiral limbus that produce otoanchorin which is defective in nonsyndromic, autosomal recessive deafness, DFNB22 (Zwaenepoel et al 2002). Scx is found in mechanically sensitive hair cells that transduce sound energy into electrical signals that subserve hearing (Hudspeth 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular defects in interdental cells, hair cells, or supporting cells in the organ of Corti are associated with auditory dysfunction (Zwaenepoel et al 2002;Zhu and Zhao 2010). Since Scx is expressed in all of these cell types, we measured auditory thresholds in Scx-null and control Scx-GFP mice.…”
Section: Hearing Loss In Scx Null Mice Is Associated With Middle Ear mentioning
confidence: 99%
“…The OTOA gene is not expressed in the brain but solely in the inner ear at the interface between the apical surface and the inner ear sensory epithelia. 72 The gene was first cloned in 2002 and it was shown that a disruptive, recessive splice site mutation in the gene lead to deafness in a large Palestinian family. 72 Affected members of the family presented a moderate to severe prelingual deafness.…”
Section: Discussionmentioning
confidence: 99%